Perancangan Meja-Kursi Belajar Ergonomis Siswa Sekolah Dasar Berbasis Pemetaan Perubahan Data Antropometri - Lia Anggara Anita; Asmungi Asmungi (Fakultas Teknik Universitas Tulang Bawang, 2023)
The optimal growth and development rate of children starts from pre-primary school age, so it is suspected that there are real differences in anthropometric data of students' bodies when they are 1 year older. If so, then for each class of elementary school students, the dimensions of the learning table-chair must also be differentiated. Different anthropometric data from grades one to six, the dimensions of the chairs and tables used during the learning process, and the unusual and uncomfortable sitting positions of students indicate that the facilities at school are not ergonomic. Therefore, it is necessary to design ergonomic facilities. This research is expected to provide certainty about the ergonomics of the dimensions of learning tables and chairs for each class in educational institutions to redesign learning tables and chairs by statistically mapping anthropometric data on the bodies of elementary school students in grades one to six to determine the ergonomic dimensions of their learning tables and chairs. The method approach used is statistical testing (One-Way Anova and Duncan). The data collection process with a sample of 240 anthropometric data and 80 musculoskeletal complaint data, the data analysis uses data uniformity test, data adequacy test, data normality test, anova, duncan, percentile and wilcoxon test. The results of this study obtained three anthropometric data mapping groups, namely group A (classes 1 and 2), group B (classes 3 and 4) and group C (classes 5 and 6). The three mapping groups were used to redesign ergonomic tables and chairs with different dimensions. The material used is teak wood and brown in color, after which the results of the redesign were tested, a decrease in musculoskeletal complaints was obtained by 32.57%. Keyword: Anthropometry, Design, Ergonomic, Mapping